On The Consequence Of Covid-19 Pandemic On Stock Price: Indonesia Case - Putri Seila Perangin-angin; Minda Muliana Sebayang; Linda Lores Purba (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
This study aims to analyze the effect of PBV, inflation, exchange rates, interest rates and transaction volume on stock prices during the Covid-19 pandemic and identify differences in stock price and transaction volume before and after the Covid-19 pandemic (Case Study on Companies Listed in IDX for the 2019-2020 period). The independent variables used in this research are PBV, inflation, exchange rate, interest rate and transaction volume. The dependent variable used is the stock price. The population used in this study are companies listed on the Indonesia Stock Exchange in 2019-2020, totaling 716 companies. This study takes samples using purposive sampling method and there are 603 companies that are considered worthy of being the research criteria. The data analysis technique used is multiple linear regression and Wilcoxon Signed Rank Test. The results showed that partially the PBV variable had a positive and significant effect on stock prices and the exchange rate variable had a significant negative effect on stock prices during the Covid-19 pandemic. Meanwhile, inflation variables, interest rates and transaction volume have no effect on stock prices during the Covid-19 pandemic. There are differences in the price and volume of stock transactions before and after the Covid-19 pandemic.